Integrated water resources management : concept, research and implementation / Dietrich Borchardt; János Bogárdi; Ralf Ibisch - Bogárdi, Jánoseditors.
This book reviews the concept, contemporary research efforts and the implementation of Integrated Water Resources Management (IWRM). The IWRM concept was established as an international guiding water management paradigm in the early 1990ies and has become a vital approach to solving the problems associated with the topic of water. The book summarizes fourteen comprehensive IWRM research projects with worldwide coverage and analyses their motivations, settings, approaches and implementation of results. Aiming to be an up-to-date interdisciplinary scientific reference, this book provides a comprehensive theoretical and empirical analysis of contemporary IWRM research, examples of science based implementations and a synthesis of the lessons learnt. It concludes with some major future challenges, the solving of which will further strengthen the IWRM concept.